Application of nanoparticle tracking analysis platform for the measurement of soot-in-oil agglomerates from automotive engines - La Rocca, Antonino; Liberto, G. Di.; Shayler, Paul J.; Parmenter, C.D.J.; Fay, M.W. (Elsevier, 2014)
Nanoparticle Tracking Analysis (NTA) has been applied to characterising soot agglomerates of particles and compared with Transmission Electron Microscoscopy (TEM). Soot nanoparticles were extracted from used oil drawn from the sump of a light duty automotive diesel engine. The samples were prepared for analysis by diluting with heptane. Individual tracking of soot agglomerates allows for size distribution analysis. The size of soot was compared with length measurements of projected two-dimensional TEM images of agglomerates. Both the techniques show that soot-in-oil exists as agglomerates with average size of 120 nm. NTA is able to measure particles in polydisperse solutions and reports the size and volume distribution of soot-in-oil aggregates; it has the advantages of being fast and relatively low cost if compared with TEM.